The application of organizational restructuring in enterprise strategic management process = Zastosowanie restrukturyzacji organizacyjnej w procesie zarządzania strategicznego przedsiębiorstwa - Kłosowski, Sławomir (Zielona Góra: Faculty of Economics and Management Press)
The aim of the paper was to present the concept of enterprise organizational restructuring process, its application in strategic management process. There was presented enterprise restructuring, its typology, areas of application in organizations with concentration on organizational restructuring process. The concept of enterprise organizational restructuring process consists of 6 main steps.
Keywords: restrukturyzacja organizacyjna; struktura organizacyjna; program restrukturyzacji; organizational restructuring; organizational structure; restructuring programme